THE SOCIALIZATION OF FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES (SAK EMKM) AND WORKSHOP ON SPREADSHEET APPLICATIONS FOR FINANCIAL REPORTS - Kosadi, Ferry; Ginting, Wajib (Universitas INABA, 2022)
The purpose of this activity is to increase knowledge and understanding of formal financial reports in accordance with SAK EMKM through socialization in the process of accounting records and preparation of financial reports as well as training using spreadsheet application software to compile financial reports with a transactional approach commonly used by business actors, namely cash disbursements and receipts with automation. the process of recording inventories, fixed assets and preparing formal financial reports in the form of Profit and Loss and Financial Position (Balance Sheet). Initial Stages of Activities, conducting several interview processes to find out the production, buying and selling processes as well as recording habits including recording fixed assets and inventories. Then proceed with the preparation of socialization materials for recording and financial reporting based on SAK EMKM and compiling an application for recording transactions with automation in making financial reports using Spreadsheet Software, namely Microsoft Excel with VBA and Macro. Furthermore, the Socialization of Recording and Preparation of Financial Reports based on SAK EMKM and Workshop on the Use of Spreadsheet Applications in Making Financial Reports was carried out. The results show that the majority of MSME actors tend not to register formally and do not make financial reports based on SAK EMKM. The preparation of financial statements is carried out when there is a need for legality related to access to funding by involving third parties in its preparation.